Selenium Pretreatment Upregulates the Antioxidant Defense and Methylglyoxal Detoxification System and Confers Enhanced Tolerance to Drought Stress in Rapeseed Seedlings - Hasanuzzaman, Mirza; Fujita, Masayuki (Biological trace element research, 2011)
In order to observe the possible regulatory role of selenium (Se) in relation to the changes in ascorbate (AsA) glutathione (GSH) levels and to the activities of antioxidant and glyoxalase pathway enzymes, rapeseed (Brassica napus) seedlings were grown in Petri dishes. A set of 10-day-old seedlings was pretreated with 25 μM Se (Sodium selenate) for 48 h. Two levels of drought stress (10% and 20% PEG) were imposed separately as well as on Se-pretreated seedlings, which were grown for another 48 h. Drought stress, at any level, caused a significant increase in GSH and glutathione disulfide (GSSG) content; however, the AsA content increased only under mild stress. The activity of ascorbate peroxidase (APX) was not affected by drought stress. The monodehydroascorbate reductase (MDHAR) and glutathione reductase (GR) activity increased only under mild stress (10% PEG). The activity of dehydroascorbate reductase (DHAR), glutathione S-transferase (GST), glutathione peroxidase (GPX), and glyoxalase I (Gly I) activity significantly increased under any level of drought stress, while catalase (CAT) and glyoxalase II (Gly II) activity decreased. A sharp increase in hydrogen peroxide (H2O2) and lipid peroxidation (MDA content) was induced by drought stress. On the other hand, Se-pretreated seedlings exposed to drought stress showed a rise in AsA and GSH content, maintained a high GSH/GSSG ratio, and evidenced increased activities of APX, DHAR, MDHAR, GR, GST, GPX, CAT, Gly I, and Gly II as compared with the drought-stressed plants without Se. These seedlings showed a concomitant decrease in GSSG content, H2O2, and the level of lipid peroxidation. The results indicate that the exogenous application of Se increased the tolerance of the plants to drought-induced oxidative damage by enhancing their antioxidant defense and methylglyoxal detoxification systems.